Abundance and habitats of marine cladocerans in the Sea of Japan over two decades. (June 2021) - Kodama, Taketoshi; Ohshimo, Seiji; Tanaka, Hiroshige; Ashida, Hiroshi; Kameda, Takahiko; Tanabe, Toshiyuki; Okazaki, Makoto; Ono, Tsuneo; Tanaka, Yosuke
Highlights: Habitats of eight species were examined based on observations over two decades. Horizontal distributions of four species were overlapped in the Sea of Japan. Steep and shallow thermocline responsible for marine cladoceran coexistence. Abstract: Marine cladocerans are secondary producers in marine neritic ecosystems. To investigate the population dynamics and species-specific habitats of marine cladocerans in the Sea of Japan, marine cladoceran abundance was evaluated in the southern Sea of Japan and the East China Sea-Kuroshio using three mesh-size (0.06, 0.10, and 0.33 mm) plankton nets at several depths ( n = 4674) over two decades from 1997 to 2018. We observed seven out of eight species, including Penilia avirostris, Evadne nordmanni, E. spinifera, Pseudevadne tergestina, and Pleopis schmackeri, from > 10% of samples, and Pleopis polyphemoides and Podon leuckartii from < 2% of samples. Abundance and diversity were higher in the Sea of Japan than in the East China Sea-Kuroshio during summer. In the East China Sea-Kuroshio, E. spinifera and Ps. tergestina abundances were high and they were distributed widely; however, other species were rare and were sparsely distributed. These suggested that the environmental conditions in the Sea of Japan are optimal for the reproduction of marine cladocerans because horizontal advective transport of marine cladocerans is not expected from the East China Sea-Kuroshio to the Sea of Japan. The habitats of the five common species in the Sea of Japan were estimated using generalized additive models (GAMs), revealing different optimal temperature ranges. Evadne nordmanni performed optimally under cold water, and the other four performed optimally under warm water. Penilia avirostris, E. spinifera, Ps. tergestina, and Pl. schmackeri coexisted in time and space in the Sea of Japan, although the vertical habitats were potentially different. Based on the estimated habitats, steep and shallow thermocline was responsible for the high marine cladoceran abundance and rich diversity in the southern Sea of Japan during summer.